Mechanism of Action Studies of Phenotypic Whole-cell Active Antimalarial Leads Through Target Identification - Korkor, Constance (Department of Chemistry, 2023)
Chemotherapy has remained the backbone of malaria control and prevention. Over the past century, potent antimalarial drugs with different mechanisms of action have been successfully developed and used to treat malaria. However, the ability of the most virulent species, P. falciparum, to resist these available antimalarial chemotypes and compromise their potency has raised the importance of using combination therapies and developing new, safe, and efficacious molecules with novel modes of action for the treatment of malaria. Phenotypic whole-cell screening, followed by medicinal chemistry optimization efforts, identified the pyrido[1,2-a]benzimidazole compounds KP68 and KP124 and the benzimidazole compound DM253 as efficacious antimalarial leads. However, the essential details of their mechanism of action against P. falciparum remain unresolved. This thesis employs ‘omics-based techniques with support from fluorescence live-cell imaging, compound docking, and heme fractionation studies to generate insights into the action of these compounds against P. falciparum. The previous mechanism of action studies on these antimalarial chemotypes has focused mainly on the inhibition of hemozoin biocrystallization in the acidic digestive vacuole of the parasite. However, the intrinsic fluorescence properties of KP68 and KP124 were used to comprehensively study the subcellular accumulation of these compounds in an infected erythrocyte. Using the inherent fluorescence properties of these compounds is advantageous because accurate localization due to the compounds is observed with no KP68 PfNF54 IC50 = 0.03 µM PfK1 IC50 = 0.04 µM in vivo P. berghei (p.o) 4x50 mg/kg = 98.0% 3/3 malaria infected mice cured KP124 PfNF54 IC50 = 0.14 µM PfK1 IC50 = 0.13 µM DM253 PfNF54 IC50 = 0.012 µM PfK1 IC50 = 0.040 µm in vivo P. berghei (p.o) 4x50 mg/kg = 99.52 Mean survival days = 14 days influence from an external fluorophore. On the other hand, DM253 required the attachment of an external fluorophore for live-cell imaging. As such, a novel fluorescent derivative was designed and synthesized with guidance from extensive structure-activity relationship studies previously conducted in this series. 7-Nitrobenz-2-oxa-1,3-diazole (NBD) was identified as an appropriate external fluorophore and was attached to the compounds investigated. The spacer chain length between the compounds and the fluorophore was varied to find suitable fluorescent derivatives that would appropriately represent the parent compounds. The photophysical and physicochemical properties of all fluorescent compounds were evaluated. Although the fluorescent derivatives lost antiplasmodium potency relative to their parent compounds, all but NBD-labelled KP124 retained antiplasmodium activity in the chloroquine-sensitive strain of P. falciparum. Furthermore, a detergent-mediated assay indicated that all fluorescently labelled derivatives retained activity against βhematin formation compared to the parent molecules. These results suggest that except for KP124-NBD, all fluorescent compounds and the fluorescent analogues were suitable for live-cell fluorescence accumulation studies. Live-cell imaging showed selective accumulation of all fluorescent compounds within P. falciparum-infected red blood cells. Different accumulation patterns were observed when using the inherent fluorescence of the structurally related KP68 and KP124. KP124 was observed to colocalize in the parasite's digestive vacuole and associate with hemozoin crystals, whiles KP68 which differs from KP124 by the replacement of the imidazole[1,2- a:4,5-b′]dipyridine core with the benzimidazole core, as well as the presence of chloro substituents, showed no accumulation in the parasite's digestive vacuole. Quantitative colocalization studies of parasite cells co-stained with KP124, DM253-NBD, and LysoTracker Red demonstrated an excellent colocalization between these signals. This indicates a preference for these compounds in the parasite's acidic compartment. Furthermore, the quantitative analysis also revealed that none of the compounds localized in the nucleus, eliminating the nucleus as a site of action for these compounds. To mitigate the limitations of resolution, Airyscan and super-resolution structured-illumination microscopy (SR-SIM) were employed. Fluorescence imaging using the ER-Tracker Red revealed a broad colocalization between KP124 and DM253-NBD and the tracker dye, suggesting that both compounds accumulate in the endoplasmic reticulum (ER). However, no significant amounts of KP68 were localized in the ER. The mitochondrion was, however, implicated in the action of KP68. Although colocalization was not observed between the MitoTracker Deep Red and KP68, significant amounts of the compound localize around the mitochondrion membrane. Finally, all compounds were assessed in the cellular heme fractionation assay. Results from this assay indicate that inhibition of hemozoin formation is a mechanism of action for KP124 but not for KP68 and DM253. The recent growth in genomics and genetics has provided powerful tools for mode of action studies. In vitro resistance selections represent one of the genomics tools for target deconvolution of hit and lead molecules. The mechanism of resistance of the pyrido[1,2- a]benzimidazoles was investigated through resistance selection. Whole-genome sequencing of the mutant clones generated from KP68 under drug pressure showed a single nucleotide polymorphism in the mitochondrion carrier protein. It also revealed a few copy number variations, including the deamplification of the mitochondrialprocessing peptidase and the P. falciparum multidrug resistance transporter PfMDR1.This result, coupled with the significant amounts of KP68 observed to accumulate around the parasite's mitochondrion, confirms the mitochondrion as an organelle of interest in the compound's mode of action in P. falciparum. Furthermore, no cross-resistance was observed between KP68 and chloroquine, suggesting that both compounds may act through different resistance mechanisms and possibly different mechanisms of action. Similarly, no cross-resistance was observed between the mutant clones generated for KP68 and KP124, meaning that the parasite's mode of resistance and the action of both compounds may be mediated through different mechanisms. This also confirms the livecell imaging and heme fractionation assay results, which support hemozoin inhibition as a mode of action for KP124 but not KP68. Finally, chemical proteomics was employed to identify the protein binding partners of these antimalarial compounds in P. falciparum. Here, drug-labelled matrices were used to capture protein binding partners of KP68 and KP124 from P. falciparum cell lysates. Several protein binding partners specific to these compounds were detected from the parasite lysate prepared and identified by mass spectrometry and proteomic analysis. Out of the many proteins identified as protein binding partners for KP68, the high molecular weight EMP1-trafficking protein, PfEMP1 is of significant interest. This is because it is essential for the parasite's survival and has been implicated in the action of other antimalarials such as dihydroartemisinin. These results suggest that these compounds may impact different parasite pathways and processes. Besides hemozoin formation, KP124 has also been implicated in interfering with the parasite's protein synthesis. Overall, this work has developed new tools that have aided in understanding the mechanistic details of these compounds. The observations described here, and further studies using the techniques and approaches to target deconvolution discussed here may facilitate the identification of novel targets for treating malaria. Also, once chemically validated, the protein targets identified in this work can serve as suitable starting points for target-based antimalarial drug discovery efforts.